Analisis Faktor Internal dan Eksternal yang Mempengaruhi Financial Distress Bank Pengkreditan Rakyat (BPR) di Indonesia pada Masa Pandemi Covid 19 - Tri Wiragil Kosasih; Nugroho Heri Pramono; Fika Azmi (ITB AAS INDONESIA, 2022)
This study aims to analyze internal and external factors that affect financial distress at BPRs in Indonesia during the covid 19 pandemic. Internal factors studied include: non-performing loans, cost income ratio, and working capital to total assets. While the external factors studied include: inflation, the rupiah exchange rate and interest rates. The population in this study is BPR registered with OJK for the period 2020. The sampling technique used is cluster sampling with the Slovin formula. The data analysis method used is multiple linear regression analysis which is processed using Eviews 11. Based on the results of data testing, the internal factor that has a positive effect on financial distress is working capital to total assets. Meanwhile, non-performing loan and cost income ratio have no effect on financial distress. In addition, the external factor that has a negative effect on financial distress is the interest rate. Meanwhile, inflation and the rupiah exchange rate have no effect on financial distress.